Lifileucel – prva celična terapija za zdravljenje melanomov - Planinšek, Pia (Placebo, 2025)
Melanoma is an aggressive form of skin cancer. Its incidence is increasing worldwide, and as advanced melanomas are often resistant to standard therapies, there is a growing need for new therapeutic approaches. One such approach is lifi leucel, the fi rst approved cell therapy with tumorinfi ltrating lymphocytes (TILs) for the treatment of unresectable or metastatic melanoma. Lifi leucel uses the patient's own T lymphocytes, which are isolated from the tumor, to specifi cally target the tumor tissue. In clinical studies, the therapy has proven eff ective in patients for whom conventional immunotherapies have failed. Approval by the U.S. Food and Drug Administration (FDA) in February 2024 is an important milestone in the treatment of solid tumors.
Keywords: celična imunoterapija; cellular immunotherapy; FDA approval; Imunoterapija; lifileucel; limfociti; lymphocytes; Melanom; melanoma; odobritev FDA; terapija s TIL; TIL therapy